Dwie krolowe : Bona i Elzbieta : powiesc historyczna - Kraszewski, Jozef Ignacy, 1812-1887. (Warszawa : Ludowa Spoldzielnia Wydawnicza, 1984)
An historical novel of the two queen consorts in the 16th century.
Keywords: Bona, -- Queen, consort of Sigismund I, King of Poland, -- 1494-1557 -- Fiction; Elzbieta, -- Queen, consort of Sigismund II Augustus, King of Poland, -- 1526-1545 -- Fiction